Identifikasi Kendala Yang Dialami Guru Dalam Menyusun Alur Tujuan Pembelajaran - Agus Prasetyo Utomo; Wahju Dyah Laksmi Wardhani; Fatchurhohman Fatchurhohman (Indonesian Journal Publisher, 2024)
The implementation of the Independent Curriculum (IKM) at the basic education level is divided into three stages of learning outcomes, namely phase A, phase B, and phase C. The flow of learning objectives (ATP) is a new way as a